Fisiologis dalam Cabang Olahraga Bola Basket: Sistematik Literatur Review - Bagus Kuncoro; Retno Farhana Nurulita; Doni Pranata; Anto Sukamto; I Putu Agus Dharma Hita (Departement of Mathematics Education, 2023)
Physiology is very important to study, especially in basketball. One of the functions of knowing the physiological parts of the sport of basketball is to ensure the health and performance of athletes during practice to competition, and can help achieve optimal results in competition. The purpose of this research is to analyze how physiological in the sport of basketball. The method used in this research is literature study by collecting information from various sources such as scientific articles from accredited journals. The results of this study are that the physiology of basketball can be divided into several aspects, including the cardiovascular system, respiratory system, musculoskeletal system, metabolic system, nervous system, and endocrine system. Through this understanding of physiology, athletes can adapt their training and diet to improve performance, prevent injury and achieve optimal results in competition.